The Happiness Level During Nursing Clinical Practice of Second Year Nursing Students - Theppradit, Piyatida; Kongpet, Jutarat; Puttakun, Nareerat (Journal of Research in Nursing-Midwifery and Health Sciences, 2023)
Objective: This study aimed to describe the happiness level of second year nursing students during nursing clinical practice Methods: The participants of descriptive study were 121 second year nursing students who had experiences of nursing clinical practice. Two instruments were used to collect data, 1) The Demographic Data Form and 2) The level of happiness in Nursing Science Bachelor’s degree questionnaire, which were examined for content validity by 3 experts. The level of happiness in Nursing Science Bachelor’s degree questionnaire, which was examined for internal consistency reliability, yielded the Cronbach’s alpha coefficient of .94. Data was analyzed using descriptive statistics. Result: The findings showed the overall mean score of happiness in second year nursing students was at high level (M = 3.98, SD = .76). Conclusion: The result of this study should be used for design the further course to increase happiness level of nursing students during nursing clinical practice.